(untitled) (Bangladesh Journal of Neuroscience, 2018)
Background: Parkinson’s disease (PD) is a common neurodegenerative disorder. Many hypotheses have been put forward for PD pathogenesis including role of lipid metabolism. Methods: This case control study was carried out in the department of neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from April 2018 to September 2019. A total of 90 persons were enrolled as study population after satisfying inclusion and exclusion criteria. Among them, 42 PD patients were grouped as cases and 48 healthy persons were controls. Results: We have compared the mean (±SD) value (mg/dl) of serum lipid variables among the cases and the controls. Serum total cholesterol in PD patients was found lower than that of control group (176.88 ± 41.12 vs 209.27 ± 43.69 mg/dl) which was statistically significant (p = 0.001) and mean (±SD) value (mg/dl) of serum LDL-C in PD patients was also found significantly lower than that of control group (107 .44 ± 39.04 vs 127.40 ± 37.83 mg/dl, p = 0.017). Serum TG levels were also significantly lower among PD patients than that of controls (152.40 ±77.86 vs 206.71 ±94.76 mg/dl, p = 0.04). Serum high-density lipoprotein cholesterol (HDL-C) levels were statistically similar among cases and controls (39.81 ± 9.79 vs 39.33 ±12.21 mg/dl, p = 0.840). Conclusion: There is an association between low serum TC, LDL-C and TG levels with PD. Further prospective studies are necessary to confirm the association. Bangladesh Journal of Neuroscience 2018; Vol. 34 (2): 66-71